2015
DOI: 10.1016/j.gdata.2015.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Annotation of suprachromosomal families reveals uncommon types of alpha satellite organization in pericentromeric regions of hg38 human genome assembly

Abstract: Centromeric alpha satellite (AS) is composed of highly identical higher-order DNA repetitive sequences, which make the standard assembly process impossible. Because of this the AS repeats were severely underrepresented in previous versions of the human genome assembly showing large centromeric gaps. The latest hg38 assembly (GCA_000001405.15) employed a novel method of approximate representation of these sequences using AS reference models to fill the gaps. Therefore, a lot more of assembled AS became availabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
112
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 42 publications
(122 citation statements)
references
References 29 publications
(77 reference statements)
10
112
0
Order By: Relevance
“…Classification of AS sequences into SFs was done using the PERCON program described in Kazakov et al (2003) and Shepelev et al (2015) and as shown in the hg38 assembly UCSC Genome Browser custom track (Shepelev et al 2015). PERCON classifies AS monomers into 12 major types (Alexandrov et al 2001) that define 5 AS SFs, of which SF1, 2 and 3 represent the live functional centromeres, and SFs 4+ and 5 represent the dead centromeric layers.…”
Section: As Suprachromosomal Family Classificationmentioning
confidence: 99%
See 4 more Smart Citations
“…Classification of AS sequences into SFs was done using the PERCON program described in Kazakov et al (2003) and Shepelev et al (2015) and as shown in the hg38 assembly UCSC Genome Browser custom track (Shepelev et al 2015). PERCON classifies AS monomers into 12 major types (Alexandrov et al 2001) that define 5 AS SFs, of which SF1, 2 and 3 represent the live functional centromeres, and SFs 4+ and 5 represent the dead centromeric layers.…”
Section: As Suprachromosomal Family Classificationmentioning
confidence: 99%
“…We also noted previously (Supplementary text S1 in Shepelev et al 2009) The program examines the alignment of a given monomer to ALPHA-ALL consensus (see details in Shepelev et al (2015)). If it does not include positions 16-26, the monomer remains unclassed ("u" in PERCON map), if it has a deletion in that region, the monomer is classed as "171 bp" and if it does not, the monomer is classed as "172 bp" (see the PERCON maps in Suppl.…”
Section: Classification Of Sf4+ Dead Layersmentioning
confidence: 99%
See 3 more Smart Citations